Assessment of Frizzled 6 membrane mobility by FRAP supports G protein coupling and reveals WNT-Frizzled selectivity - Kilander, Michaela B C; Dahlström, Jenny; Schulte, Gunnar (Cellular signalling, 2014)
The WNT receptors of the Frizzled family comprise ten mammalian isoforms, bind WNT proteins and mediate downstream signaling to regulate stem cell fate, neuronal differentiation, cell survival and more. WNT-induced signaling pathways are either β-catenin-dependent or -independent, thereby dividing the 19 mammalian WNT proteins into two groups. So far hardly any quantitative, pharmacological information is available about WNT-FZD interaction profiles, affinities or mechanisms of signaling specification through distinct WNT/FZD pairings. This lack of knowledge originates from difficulties with WNT purification and a lack of suitable assays, such as ligand binding assays and FZD activity readouts. In order to minimize this gap, we employ fluorescence recovery after photobleaching (FRAP) to investigate WNT effects on the lateral mobility of FZD6-GFP in living cells. Pharmacological uncoupling of heterotrimeric G proteins by pertussis toxin and N-ethylmaleimide argues that changes in FZD6 mobility are related to putative precoupling of heterotrimeric Gi/o proteins to FZD6. We show that recombinant WNT-1, -2, 3A, -4, -5A, -7A, -9B and -10B affect FZD6 surface mobility and thus act on this receptor. WNT-5B and WNT-11, on the other hand, have no effect on FZD6 mobility and we conclude that they do not act through FZD6. We introduce here a novel way to assess WNT-FZD interaction by live cell imaging allowing further mapping of WNT-FZD interactions and challenging previous experimental limitations. Increased understanding of WNT-FZD selectivity provides important insight into the biological function of this crucial signaling system with importance in developmental biology, stem cell regulation oncogenesis, and human disease.
Keywords: buněčná membrána; signální transdukce; Signal Transduction; Heterotrimeric GTP-Binding Proteins; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; proteiny Wnt; protein Wnt 5a; Fluorescence recovery after photobleaching; Pertussis Toxin; Fluorescence Recovery After Photobleaching; WNT signaling; Wnt Proteins; Wnt-5a Protein; GPCRs; lidé; HEK293 Cells; Recombinant Proteins; protoonkogenní proteiny; proteiny vázající GTP - alfa-podjednotky Gi-Go; pertusový toxin; rekombinantní proteiny; Ethylmaleimide; Class Frizzled; frizzled receptory; HEK293 buňky; Proto-Oncogene Proteins; ethylmaleimid; heterotrimerní G-proteiny; FRAP; Cell Membrane; Heterotrimeric G proteins; Frizzled Receptors